Consumer online browsing: conceptual definition, theoretical and managerial implications - Sandes, Fábio Shimabukuro (2020)
Consumer Online Browsing (COB) is a distinct behavior in consumer behavior literature that needs further research in literature. This dissertation aims to conceptually define COB and discuss theoretical and managerial implications of COB for consumers. This dissertation begins with a theoretical study about compulsiveness, a topic that has been extensively discussed in consumer behavior literature, with most of studies focused on the purchase stage. Both pre and post purchase stages, however, have gained relevance in marketing literature due to the multiple touch points consumers have to connect with brands, and companies. This dissertation is composed of three articles. The first applies the consumer journey framework to assess how compulsiveness is being discussed in these stages with the objective of proposing a research agenda for future studies. One of the topics that is in lack of research is browsing, and this is the connection to the following studies presented in this dissertation. Consumer online browsing (COB) is not conceptualized as a distinct behavior in literature, as it is often discussed as offline browsing, or exploratory search. It includes, however, characteristics that show its uniqueness. One exploratory qualitative study compared online with offline browsing, and listed characteristics that distinguish these behaviors. A survey with 517 participants in Brazil and in the US was conducted and results showed that COB is a distinct because in comparison with offline browsing leads to more product knowledge, increases purchase intention, promotes serendipity findings in products and brands, and does not lead to impulsive, unplanned buying, as it happens with offline browsing. In the third article three experiments were conducted with participants in Brazil and US, and results showed that COB leads to an increase in product knowledge and purchase intention. When there is a high involvement with the product and the motivation for browsing is hedonic, the impact on both variables is intensified.